2012
DOI: 10.1055/s-0032-1304591
|View full text |Cite
|
Sign up to set email alerts
|

‘Nordic’ Hamstrings Exercise – Engagement Characteristics and Training Responses

Abstract: The present study examined the neuromuscular activation characteristics of the hamstrings during the ?Nordic? hamstrings exercise (NHE) and changes in the eccentric strength of the knee flexors with NHE training. Initially, the normalised root mean square electromyographic (EMG) activity of the hamstrings of both limbs during various phases (90?61?, 60?31? and 30?0? of knee extension) of the NHE were determined in 18 soccer players. Subsequently participants were randomly allocated to either a training (n=10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 18 publications
(38 reference statements)
6
95
4
4
Order By: Relevance
“…Additionally, when fascicle increases have been shown to occur, they increase fairly quickly; 3-5 weeks into eccentric training (Blazevich et al 2007;Baroni et al 2013;Guex et al 2016;Bourne et al 2016). The current NH intervention length of 6 weeks was similar to previous studies (Iga et al 2012;Delahunt et al 2016). Given these findings it seems unlikely that an increase in muscle fascicle length is responsible for the injury protection provided by NH exercise.…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archsupporting
confidence: 82%
See 4 more Smart Citations
“…Additionally, when fascicle increases have been shown to occur, they increase fairly quickly; 3-5 weeks into eccentric training (Blazevich et al 2007;Baroni et al 2013;Guex et al 2016;Bourne et al 2016). The current NH intervention length of 6 weeks was similar to previous studies (Iga et al 2012;Delahunt et al 2016). Given these findings it seems unlikely that an increase in muscle fascicle length is responsible for the injury protection provided by NH exercise.…”
Section: Effects Of Nordic Hamstring Strength Training On Muscle Archsupporting
confidence: 82%
“…Over a 4-week NH intervention, Clark et al (2005) showed an approximate 6° shift in the angle of peak concentric torque towards knee extension. In contrast to these two reports, the knee angle of peak eccentric hamstring torque was unchanged following 4 and 6 week NH interventions (Iga et al 2012, Delahunt et al 2016. Only one study to date has directly evaluated hamstring length adaptations following a NH strength intervention, showing a 20.8% fascicle length increase after 10-weeks (Bourne et al 2016).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations